Digital Learning Innovation: Implementation of Autoplay Studio in Teaching Islamic Religious Education at Elementary School - Hafsah, Siti; Mashudi, Mashudi; Muhith, Abd (Program Studi PGMI, 2025)
This study examines the implementation of Autoplay Studio in teaching Islamic Religious Education (IRE) at SDN 21 Dauh Puri Denpasar. Using a qualitative approach, the research explores the experiences, perceptions, and challenges faced by teachers and students in integrating digital learning tools. Data were collected through classroom observations, semi-structured interviews, and document analysis, then analyzed using thematic analysis techniques. The findings indicate that the use of Autoplay Studio enhances student engagement, comprehension of religious concepts, and overall learning effectiveness. Interactive features such as animations and digital quizzes increase student motivation and participation. Teachers reported that digital media simplified complex religious concepts, although challenges related to infrastructure and digital literacy were observed. This study supports multimedia learning and social constructivism theories, which emphasize the importance of interaction and hands-on experiences in education. Despite challenges in adopting digital technology, the findings suggest that Autoplay Studio has the potential to improve the quality of IRE instruction in elementary schools. Key recommendations include enhancing teacher training and digital infrastructure to optimize technology integration in religious education.